Parseval's Identity for Low-Dimensional Nilpotent Lie Groups G5,1, G5,2, G5,3 and G5,5 - Bhatta, CR (Kathmandu University Journal of Science Engineering and Technology, 2009)
We prove the Parseval's identity for low-dimensional nilpotent Lie groups such as G5,1, G5,2, G5,3 and G5,5 respectively which are important for proving Hardy uncertainty principles type result.